Introgression Leads to Genomic Divergence and Responsible for Important Traits in Upland Cotton - He, Shoupu; Wang, Pengpeng; Zhang, Yuan-Ming; Dai, Panhong; Nazir, Mian Faisal; Jia, Yinhua; Peng, Zhen; Pan, Zhaoe; Sun, Junling; Wang, Liru; Sun, Gaofei; Du, Xiongming (Frontiers in Plant Science, 2020)
Understanding the genetic diversity and population structure of germplasms is essential when selecting parents for crop breeding. The genomic changes that occurred during the domestication and improvement of Upland cotton (Gossypium hirsutum) remains poorly understood. Besides, the available genetic resources from cotton cultivars are limited. By applying restriction site-associated DNA marker sequencing (RAD-seq) technology to 582 tetraploid cotton accessions, we confirmed distinct genomic regions on chromosomes A06 and A08 in Upland cotton cultivar subgroups. Based on the pedigree, reported QTLs, introgression analyses, and genome-wide association study (GWAS), we suggest that these divergent regions might have resulted from the introgression of exotic lineages of G. hirsutum landraces and their wild relatives. These regions were the typical genomic signatures that might be responsible for maturity and fiber quality on chromosome A06 and chromosome A08, respectively. Moreover, these genomic regions are located in the putative pericentromeric regions, implying that their application will be challenging. In the study, based on high-density SNP markers, we reported two genomic signatures on chromosome A06 and A08, which might originate from the introgression events in the Upland cotton population. Our study provides new insights for understanding the impact of historic introgressions on population divergence and important agronomic traits of modern Upland cotton cultivars.